Comparison of pattern of self-medication among urban and rural population of Telangana state, India - Pentareddy, Mary Rohini; Vedula, Prasanna; B., Roopa; L., Jagadish Chandra; Amarendar, S. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Self-medication is one of the components of self-care, which may treat the disease or result in worsening of the condition due to irrational use of drug.1 In developing countries like India, self-medication is a common practice as it provides a low-cost alternative for people who cannot afford the high cost of clinical service, and is time efficient. Methods: A total of 110 participants completed the study. A printed questionnaire was given to those who were willing to participate in the study and came to buy medicines without consulting a doctor to various pharmacy outlets. Results: Among the group of drugs used antibiotics were the common drugs used in rural area (74%) and cough suppressants (50%) in urban area. Symptoms for opting self-medication were fever and common cold in both the groups. Individuals in both areas took self-medication based on their previous prescriptions (rural 42% vs urban41.6%) and advertisements. Rural individuals preferred self-medication with the opinion of saving time and urban people felt that it was less expensive. Conclusions: There is a difference in the pattern self-medication among rural and urban individuals. It is also to be noted that use of antibiotics may result in problems related to drug resistance. So, it would be advisable to restrict the sale of antibiotics as over the counter drugs.